If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.08(x + -1) = 2x Reorder the terms: 0.08(-1 + x) = 2x (-1 * 0.08 + x * 0.08) = 2x (-0.08 + 0.08x) = 2x Solving -0.08 + 0.08x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -0.08 + 0.08x + -2x = 2x + -2x Combine like terms: 0.08x + -2x = -1.92x -0.08 + -1.92x = 2x + -2x Combine like terms: 2x + -2x = 0 -0.08 + -1.92x = 0 Add '0.08' to each side of the equation. -0.08 + 0.08 + -1.92x = 0 + 0.08 Combine like terms: -0.08 + 0.08 = 0.00 0.00 + -1.92x = 0 + 0.08 -1.92x = 0 + 0.08 Combine like terms: 0 + 0.08 = 0.08 -1.92x = 0.08 Divide each side by '-1.92'. x = -0.04166666667 Simplifying x = -0.04166666667
| 0.08(x-1)=2 | | x^2+y^2=55 | | 5/4/10/3 | | x^2-48=(x-8)(x-6) | | 3k^2-26k=16 | | x^3-16x+4x-16= | | 2k^2+11k-63=0 | | 140=2x(3x-1) | | -2=3x-14/4= | | 7+7x=7(1+x) | | 15=5625 | | 0.1(x+30)+0.1x= | | -2=3x-14/4 | | 5x+3(4x-11)=52 | | 126+x+23=x+37 | | 5x-28=83 | | 9x+10y=7 | | x^3+3x^2-6x-18=0 | | 15c^3+5c^2-120c= | | (4x+12)=2x | | -6x+4y=24 | | 2x+.5x+20=80 | | 1x+3x-2=90 | | 7x-2x=110 | | X^4=x^3-9x^2 | | -x^(-1/3)*e^(-x)*(x-2/3)=0 | | 10(x-2)=-2 | | f(x)=e^15x | | 10-x=-10 | | 2x+3(1.3-x)=(-1.35) | | -5(-u-4w+3)= | | x+(3x+12)=180 |